La discrétion administrative et la mise en oeuvre d'une politique - Atkinson, William (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
This article deals with the relationships between the exercise of administrative discretion and the implementation of a policy. Chapter I defines administrative discretion as a power to make a choice in a particular case. This choice may be technical or political but in both instances relates to the implementation of a policy. The exercise of discretion is also situated within a system under the Rule of Law using H.L.A. Hart's concepts of primary and secondary rules. Chapter II deals with the exercise of discretion in relation to policy. First, if refers to K.C. Davis' model of confining, structuring and checking discretion. To confine discretion is to set the limits within which it should be exercised. To structure it is define the manner by which it is to be exercised notably in opening the decision-making process. To check discretion is to subject the decision to another authority. The next three sections of this chapter are concerned with legislative, regulatory and administrative policy. The first section studies legislative expressions of policy and their impact on the exercise of discretion. Secondly, the question of the choice between regulation and administrative discretion is analysed as is the control over that choice and the nature of regulation over it is decided to adopt it. Finally, the impact of an administrative discretion is seen when attacked by the citizen on the grounds that it fetters discretion, constitutes bias or when relied upon by the citizen. It is seen that in most cases, the administrator may structure his discretionary power in a manner respected by the courts.